UNIVERSAL SERVICES IN EU LAW IN THE ERA OF LIBERALIZATION - Maziarz, Aleksander (European Scientific Journal, ESJ, 2015)
Universal services were used in many laws as a form of state intervention. The European lawmaker also introduced this concept to guarantee the provision of certain services to all citizens in all Member States. However, liberalization of different sectors of the economy strengthens competition and removes state monopolies. The aim of this article is to determine whether the concept of universal services is still needed. Doubts about the need for that concept arise because of another European concept of services of general economic interest, which enables particular Member States to introduce certain public services. The article will focus on several sectors of the economy in which universal services were introduced and will try to justify maintaining such services.